El dios Dancerus de la cañada de Remeseiros (Vilar de Perdizes, Montealegre, Portugal), un Silvano indígena protector de los contratos de arrendamiento (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This brief article presents and deals with our hypothesis for the ultimate interpretation of the great inscription found in Remeseiros, Vilar de Perdizes (Portugal).
Keywords: Remeseiros; Dancerus; Callida; Reburrus; Roman Inscriptions